Survey of the fecal microbiota of indigenous small ruminants living in different areas of Guizhou - Guo, Wei; Liu, Tingmei; Wang, Weiwei; Yu, Yinshu; Neves, André Luis Alves; Zhou, Mi; Chen, Xiang (Frontiers in Microbiology, 2024)
The gut microbiota is associated with the health and performance of ruminant species. To explore how fecal microbiota of small ruminants differ among animal populations, here we characterized the fecal microbiota in two goat breeds and one sheep breed distributed across sex groups (males and females). We employed 16S rRNA sequencing to profile the fecal bacteria in Hei and Qianbei Ma goats and Weining sheep in the Chinese of Guizhou province. The fecal microbial profile varied with herd (genetics/altitude) and sex. All samples were categorized into two enterotypes, with the UCG-005 and Christensenellaceae_R-7_group dominating enterotypes 1 and 2 respectively, which may be highly driven by host genetics (breed). The predicted functional profiles of fecal microbiota were also assigned to two clusters that corresponded exactly to the enterotypes. Cluster 1 of the functional profiling was characterized by biosynthesis pathways and cluster 2 by energy metabolism pathways. In conclusion, this study unveiled both the bacterial fecal microbiota profile and the constitution of fecal enterotypes in goats and sheep breeds in Guizhou. Our findings may provide new insight into fecal microbial community and enterotypes in small ruminant by herds, which offers clues for deciphering the mechanisms of the fecal microbiota contributes to the divergent host phenotypes in indigenous small ruminants in Guizhou.